The effect of the spin–orbit coupling on the physical properties of ScGa3 and LuGa3 superconductors. (April 2023) - Tütüncü, H.M.; Karaca, Ertuǧrul; Baǧcı, S.; Uzunok, H.Y.
Abstract: In this work, we have aimed to reveal the impacts of spin–orbit coupling (SOC) on the elastic, mechanical, electronic, phonon, and electron–phonon interaction properties of ScGa 3 and LuGa 3 by executing both scalar and full-relativistic ab initio pseudopotential calculations based on the density functional theory with its local density approximation. The effect of this coupling on the physical properties of LuGa 3 is slightly more pronounced than those of ScGa 3 . This finding has a physical explanation because spin–orbit interaction in an atom is due to the interaction of electronic spin moment with the magnetic field formed by the traveling electron in the electric field of the nucleus. Since the nuclear charge enhances with the rise in atomic number of the elements, heavier atoms are characterized by larger SOC strength and the mass of Lu atom is considerably heavier than that of Sc atom. In particular, the inclusion of SOC changes the value of the electron–phonon coupling parameter for LuGa 3 from 0.593 to 0.583 by less 2%, while the corresponding parameter of ScGa 3 remains almost unchanged (from 0.536 to 0.537). The superconducting transition temperature is estimated to be 2.09 K for ScGa 3, and 2.15 K for LuGa 3 are almost equal to their experimental values of 2.1 and 2.2 K, respectively. Finally, we have estimated three superconducting parameters: the Ginzburg–Landau parameter ( κ (0)), the London penetration depth ( λ L ( 0 ) ) and the coherence length ( ξ ( 0 ) ). Their calculated values confirm the existence of type-I superconductivity in both superconductors. Highlights: The impacts of spin–orbit coupling physical properties of ScGa 3 and LuGa 3 are studied at 0.0 GPa. The effect of this coupling found to be more effective on LuGa3 than ScGa3. The λ parameter of ScGa 3 remains almost unchanged under SOC. All the studied superconductors possess s-wave pairing symmetry.